Liberia : Fourth Review Under the Extended Credit Facility Arrangement and Requests for Waivers of NonObservance of Performance Criteria, Modification of Performance Criteria, and Rephasing and Extension of the Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Liberia. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Liberia's Fourth Review Under the Extended Credit Facility (ECF) Arrangement and Requests for Waivers of Nonobservance of Performance Criteria (PC), Modification of PC, and Rephasing and Extension of the Arrangement. The end-June 2014 quantitative PC on government revenues and central bank net foreign exchange position, and one indicative target on net domestic assets were not met. Only three out of seven structural benchmarks for the fourth review were met. Based on the authorities' corrective actions, the IMF staff supports completion of the delayed fourth ECF review, and the authorities' request for an extension and re-phasing of the program to end-December 2016.